Glycine receptor autoantibody binding to the extracellular domain is independent from receptor glycosylation - Rauschenberger, Vera; Piro, Inken; Kasaragod, Vikram Babu; Hörlin, Verena; Eckes, Anna-Lena; Kluck, Christoph J.; Schindelin, Hermann; Meinck, Hans-Michael; Wickel, Jonathan; Geis, Christian; Tüzün, Erdem; Doppler, Kathrin; et al. (Frontiers in Molecular Neuroscience, 2023)
Glycine receptor (GlyR) autoantibodies are associated with stiff-person syndrome and the life-threatening progressive encephalomyelitis with rigidity and myoclonus in children and adults. Patient histories show variability in symptoms and responses to therapeutic treatments. A better understanding of the autoantibody pathology is required to develop better therapeutic strategies. So far, the underlying molecular pathomechanisms include enhanced receptor internalization and direct receptor blocking altering GlyR function. A common epitope of autoantibodies against the GlyRα1 has been previously defined to residues 1A-33G at the N-terminus of the mature GlyR extracellular domain. However, if other autoantibody binding sites exist or additional GlyR residues are involved in autoantibody binding is yet unknown. The present study investigates the importance of receptor glycosylation for binding of anti-GlyR autoantibodies. The glycine receptor α1 harbors only one glycosylation site at the amino acid residue asparagine 38 localized in close vicinity to the identified common autoantibody epitope. First, non-glycosylated GlyRs were characterized using protein biochemical approaches as well as electrophysiological recordings and molecular modeling. Molecular modeling of non-glycosylated GlyRα1 did not show major structural alterations. Moreover, non-glycosylation of the GlyRα1N38Q did not prevent the receptor from surface expression. At the functional level, the non-glycosylated GlyR demonstrated reduced glycine potency, but patient GlyR autoantibodies still bound to the surface expressed non-glycosylated receptor protein in living cells. Efficient adsorption of GlyR autoantibodies from patient samples was possible by binding to native glycosylated and non-glycosylated GlyRα1 expressed in living not fixed transfected HEK293 cells. Binding of patient-derived GlyR autoantibodies to the non-glycosylated GlyRα1 offered the possibility to use purified non-glycosylated GlyR extracellular domain constructs coated on ELISA plates and use them as a fast screening readout for the presence of GlyR autoantibodies in patient serum samples. Following successful adsorption of patient autoantibodies by GlyR ECDs, binding to primary motoneurons and transfected cells was absent. Our results indicate that the glycine receptor autoantibody binding is independent of the receptor’s glycosylation state. Purified non-glycosylated receptor domains harbouring the autoantibody epitope provide thus, an additional reliable experimental tool besides binding to native receptors in cell-based assays for detection of autoantibody presence in patient sera.